Cationic copolymer, nano-microsphere as well as preparation method and application of nano-microsphere

By using cationic copolymers and nano-microspheres with hydrophilic, lipophilic and CO2-philic characteristics in the supercritical CO2 oil flooding process, supercritical CO2 and water are self-emulsified, and in-situ collaborative regulation is achieved through the release mechanism of the nano-microspheres. , solves the impact of formation water on CO2 migration and miscible oil displacement process, and improves oil recovery.

CN119350548AInactive Publication Date: 2025-01-24BEIJING INSTITUTE OF PETROCHEMICAL TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411468801.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the supercritical CO2 oil flooding process, formation water has a great impact on CO2 migration and mixed phase oil flooding process, resulting in low displacement efficiency, and it is difficult for the existing technology to effectively solve this problem.

Method used

Adopt a cationic cluster that is obtained by a monomer A, single B, and monomer C, and combined with the anion polymer to prepare nano -balls. The cedic co -concentration has a variety of affinity with hydrophilic, parenting oil, and pro -CO2. In the oilfield strata, the supercritical CO2 and water are emulsified, and the coordinated regulation is achieved through the release mechanism of the nano -golf.

Benefits of technology

It achieves the formation of a stable CO2/water emulsion in harsh reservoir environments, enhances the miscibility efficiency of CO2 and crude oil, improves oil recovery, and avoids the negative impact of formation water on CO2 migration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350548A_ABST
    Figure CN119350548A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of CO2 oil displacement, in particular to a cationic copolymer, a nano-microsphere, a preparation method of the nano-microsphere and application of the nano-microsphere. According to the cationic copolymer, supercritical CO2 and water can be self-emulsified under the oil field stratum condition to form stable emulsion; the cationic copolymer has a positively charged hydrophilic chain link structure, a CO2-philic chain link structure and a propyl alcohol type lipophilic chain link structure at the same time, and has various affinity characteristics of hydrophilicity, lipophilicity and CO2 affinity in a supercritical CO2 fluid. Therefore, the cationic copolymer provided by the invention can form a CO2 / water emulsion when encountering formation water in a relatively severe complex reservoir environment, and the emulsion is subjected to a mixed-phase process when encountering oil to form a quasi-mixed state. The quasi-mixed state can solve the key problem of stratum water influence in the aperture system, the effect of replacing crude oil with CO2 in the matrix is further enhanced, and the crude oil recovery rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of CO2 oil displacement, in particular to a cationic copolymer, nano-microspheres and a preparation method and application thereof. Background Art

[0002] In order to achieve the goal of "carbon peak and carbon neutrality" (referred to as "dual carbon"), a series of carbon capture, utilization and storage (CCUS) measures being taken by various industries are considered to be one of the effective ways to reduce carbon emissions. As one of the CCUS technologies in the field of oil and gas development, carbon dioxide enhanced oil recovery (CO2-EOR) technology has developed rapidly due to its advantages such as good injectability, high oil recovery efficiency and CO2 storage rate. CO2-EOR technology is divided into CO2 immiscible drive and CO2 miscible drive according to the degree of miscibility between the displacement agent (injected gas) and crude oil. Immiscible drive has low sweep efficiency and poor oil recovery effect due to the large gas-liquid density difference and capillary force. Miscible drive refers to the diffusion and mass transfer of the displacement agent (injected gas) and crude oil, and their mutual dissolution, eliminating the surface, so that the oil displacement agent and crude oil form a single miscible state. At this time, the capillary retention and closure effect of crude oil disappears, and the oil recovery efficiency is higher than that of immiscible drive, which is the main development direction at present. Research and practice have shown that injecting compressed liquid CO2 into the formation and controlling the CO2 to exist in a supercritical state under reservoir temperature and pressure conditions to form a miscible oil recovery method has the best oil recovery efficiency and storage efficiency. Promoting the large-scale application and development of CO2 recovery has great strategic and economic significance.

[0003] In the 1980s, with the development of natural CO2 gas fields in the United States and the laying of gas pipelines, several oil fields such as Paradis and Shoemaker successively carried out CO2 injection development experiments, and CO2 flooding has gradually become the main means of improving oil recovery in North America. In foreign mine field experiments, CO2 flooding technology is still mainly based on miscible flooding, accounting for more than 90%; China's continental sedimentary reservoir environment is more complex, with stronger heterogeneity, and most oil reservoirs have higher temperatures. Crude oil is mainly composed of heavy components, C2-C 15 The component content is obviously low, the crude oil viscosity is high, and the supercritical CO2 front can easily break through the underground fluid to form crossflow, which increases the difficulty of supercritical CO2 and residual oil mixing. Not only that, as the proportion of residual oil decreases, the proportion of formation water in the pore system increases significantly. The supercritical CO2 / crude oil miscibility process is easily affected by underground fluids such as formation water, and the ideal single miscible state is difficult to achieve. It has a great impact on the displacement efficiency of supercritical CO2 flooding.

[0004] Research on supercritical CO2 flooding mainly focuses on regulating CO2 mobility to improve sweep efficiency and improving the miscibility of CO2 and crude oil. Research on how to eliminate the important influence of objectively existing formation free water on supercritical CO2 migration and miscible flooding is urgently needed. Basic research on supercritical CO2-water emulsions in the field of CO2 displacement and exploitation of natural gas hydrates provides a new approach to solving this problem. The CO2-water emulsification process can convert free formation water into the dispersed phase of the emulsion, minimizing its negative impact on the supercritical CO2 / crude oil miscibility process.

[0005] However, the application of CO2 emulsions in oil and gas production is still in its infancy. The basic research on the application of CO2-water emulsions in the field of oil and gas production mainly focuses on the use of CO2 to replace natural gas hydrates. In 2012, ConocoPhillips completed the world's first field test project on the potential of CO2 / CH4 replacement in the West Sak well area of ​​the North Slope Oil Field in Alaska. In order to enhance the efficiency of CO2 / CH4 replacement, Zhou et al. tried to prepare gaseous CO2-water microfoam and supercritical CO2-water emulsions with different water-carbon ratios in 2008, and found that the replacement rate of CO2 emulsions for hydrates was higher than that of pure supercritical CO2. In 2014, Yuan et al. formed a CO2-water emulsion using sodium dodecyl sulfate and polyoxyethylene sorbitan monooleate as emulsifiers, and found that its stability was mainly affected by temperature, pressure and mineralization. In 2021, Yan Yu and others tried the emulsion stability under different initial components and reaction conditions, and screened out octylphenol-10 (OP-10), which has better CO2 emulsion stability than Tween 80 and sorbitan monopalmitate emulsifier systems in previous experiments. Although it has been developed for more than ten years, the application of CO2 emulsions in oil and gas extraction is still in its infancy. Due to the limitations of natural gas applications, supercritical CO2 emulsions must be prepared before injection. However, due to the limitations of the temperature and pressure gradient of terrestrial oil field reservoirs, this method cannot be directly copied to the field of supercritical CO2 oil recovery. There are no reports on the use of emulsification to enhance mass transfer in improving the miscibility of CO2 / crude oil, and research on the formation and enhanced mass transfer mechanism of CO2 emulsions in terrestrial sedimentary reservoir environments is urgently needed. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a cationic copolymer, nano-microspheres and their preparation method and application, wherein the cationic copolymer can enable supercritical CO2 to be well emulsified with water in oil field formations, and the nano-microspheres made of the cationic copolymer and the anionic polymer have a sustained release effect, and can be injected into the oil field formation together with the supercritical CO2, thereby realizing the in-situ coordinated regulation of the supercritical CO2 emulsion.

[0007] In order to achieve the above technical effects, the present invention adopts the following technical solutions:

[0008] A cationic copolymer is prepared by copolymerizing monomer A, monomer B and monomer C, wherein the average molecular weight of the cationic copolymer is 1000Da-25000Da.

[0009] The molar ratio of monomer A, monomer B and monomer C is (3-8):(1.5-2.5):(2-4),

[0010] Wherein, monomer A is selected from at least one of dimethyldiallyl ammonium chloride (DMDAAC), dimethylaminoethyl methacrylate (DMAEMA), vinyl pyrrolidone (NVP) or cationic acrylamide (AM), monomer B is propylene oxide, and monomer C is selected from at least one of dimethyldiallyl ammonium chloride (DMDAAC), dimethylaminoethyl methacrylate (DMAEMA), perfluoroacrylate (TPA), 1H,1H,2H,2H-perfluorodecyl acrylate (FDA) or hexafluorobutyl methacrylate (HFBMA).

[0011] In the cationic copolymer, monomer A is a CO2-philic monomer, monomer B is a lipophilic monomer, and monomer C is a cationic monomer.

[0012] The cationic copolymer provided by the present invention can make supercritical CO2 and water self-emulsify under oil field formation conditions to form a stable emulsion. The cationic copolymer has a positively charged hydrophilic chain segment structure, a CO2-philic chain segment structure and a propanol-type lipophilic chain segment structure, and has multiple affinity characteristics of hydrophilicity, lipophilicity and CO2-philicity in the supercritical CO2 fluid. Therefore, the cationic copolymer provided by the present invention can form a CO2 / water emulsion when encountering formation water in a relatively harsh reservoir complex environment, and the emulsion undergoes a miscible process when encountering oil to form a pseudo-mixed state. The pseudo-mixed state can solve the key problem of the influence of formation water in the pore system, further enhance the effect of CO2 replacing crude oil in the matrix, and improve the recovery rate of crude oil.

[0013] Preferably, in the cationic copolymer, the molar ratio of monomer A, monomer B and monomer C is (3.5-6):(2-2.5):(3-3.6).

[0014] Preferably, monomer A is selected from dimethyldiallylammonium chloride (DMDAAC), dimethylaminoethyl methacrylate (DMAEMA) or vinyl pyrrolidone (NVP); monomer C is selected from dimethyldiallylammonium chloride (DMDAAC) or dimethylaminoethyl methacrylate (DMAEMA).

[0015] More preferably, when the monomer A is dimethyldiallylammonium chloride (DMDAAC) or dimethylaminoethyl methacrylate (DMAEMA), the monomer C is not required, and the molar ratio of the monomer A to the monomer B remains unchanged.

[0016] Preferably, the preparation method of the cationic copolymer is as follows:

[0017] The initiator is dissolved in the first organic reagent to obtain an initiator solution, the monomer A, the monomer B and the monomer C are dissolved in the second organic solvent, the initiator solution is added and mixed, nitrogen is passed through to deoxygenate, and then the cationic copolymer is obtained by copolymerization through a hydrothermal reaction.

[0018] Preferably, the initiator is at least one of ammonium persulfate (APS), 4,4-azobis(4-cyanovaleric acid) (ACPA), and azobisisobutyronitrile (AIBN);

[0019] The first organic reagent is tetrahydrofuran (THF);

[0020] The second organic agent is selected from any one of cyclohexane, heptane (HPT), octane or kerosene;

[0021] The hydrothermal reaction temperature is 45°C-65°C;

[0022] The mass ratio of initiator to monomer B is (0.02-0.12):1.

[0023] The present invention also provides a nano-microsphere, which is prepared by reacting an anionic polymer and at least one cationic copolymer, wherein the molar ratio of the anionic polymer to the cationic copolymer is (1.28-0.69):1;

[0024] The reactions include electrosorption and cross-linking;

[0025] The anionic polymer is selected from at least one of sodium polyvinyl sulfate (Na-PVS), polyacrylic acid (PAA), polyanionic cellulose PAC, polyanionic cellulose DRISPAC, or carboxymethyl cellulose (CMC); in the selection of the anionic polymer, the effects that can be achieved by each anionic polymer are basically similar;

[0026] The average particle size of the nanospheres is 150nm-600nm.

[0027] Preferably, the anionic polymer is Na-PVS.

[0028] The preparation method of the nano-microspheres is as follows: the cationic copolymer and the anionic polymer are respectively put into a solvent to prepare a cationic dispersion and an anionic dispersion, the cationic dispersion is added dropwise to the anionic dispersion, and the nano-microspheres are obtained by concentration and washing after the reaction.

[0029] Preferably, the solvent in the cationic dispersion is deionized water; the solvent in the anionic dispersion is deionized water; further preferably, the mass concentration of the cationic copolymer in the cationic dispersion is 0.01wt%-1.10wt%, and the mass concentration of the anionic polymer in the anionic dispersion is 0.01wt%-1.50wt%.

[0030] Preferably, the dropping speed is 60-90 drops / min.

[0031] The preparation method of the nanospheres also includes: adding the nanospheres into a stabilizer solution to prepare a nanosphere dispersion with a mass concentration of 0.01wt%-1.50wt% for standby use; further preferably, the stabilizer is a Poloxmar (Pluronic F-127) non-ionic surfactant; more preferably, the stabilizer concentration in the stabilizer solution is 0.02wt%-0.2wt%, and the solvent in the stabilizer solution is deionized water.

[0032] The storage time can be prolonged by adding a stabilizer into the nanosphere dispersion.

[0033] The present invention also provides the use of the nano-microspheres or the nano-microspheres prepared by the above preparation method in supercritical CO2 flooding to improve the recovery rate. The nano-microspheres are put into supercritical CO2 and injected into the oil field reservoir, and the oil field reservoir has a crossflow channel.

[0034] Preferably, the mass ratio of nanospheres to supercritical CO2 is (0.05-4.5):100; further preferably, the nanospheres are added directly and / or in the form of a nanosphere dispersion.

[0035] The nano-microspheres provided by the present invention enter the reservoir with the supercritical CO2, and then migrate underground with the supercritical CO2. Crossflow channel The free water in the crossflow channel changes the surface electrical properties and pH value of the nano-microspheres after contacting them, causing the nano-microspheres to swell, dissociate and release the cationic copolymers, and deprotonate the charged functional groups of the cationic copolymers, thereby realizing the function of "targeted release" of the cationic copolymers in response to the environment when CO2 migrates; the entire process of swelling, dissociation and release of the cationic copolymers takes several hours to dozens of hours, which is determined by the composition, particle size and chemical properties of the free water in the crossflow channel of the nano-microspheres; the released cationic copolymers can stimulate the in-situ self-emulsification of supercritical CO2 and formation water to form a CO2-water emulsion to achieve in-situ thickening of CO2, and the emulsion can also promote the miscibility of CO2 / crude oil after encountering oil, thereby realizing the in-situ coordinated regulation of supercritical CO2 oil displacement self-emulsification thickening / directional mass transfer miscibility.

[0036] The nano-microspheres provided by the present invention are nano-scale microsphere materials with uniform structure or core-shell structure formed by cationic copolymers and anionic polymers through electrical adsorption, and their structural characteristics are regulated by the chain length, charge density and polarity of the cationic copolymers and anionic polymers. The nano-microspheres have a particle size of 150nm-600nm, and when used in unconventional low-permeability reservoirs such as tight sandstones and shales, they can have good dispersibility and reservoir migration capacity.

[0037] After the nano-microspheres are injected into the oil field reservoir, the nano-microspheres meet water, and the CN bonds of the quaternary ammonium groups on the cationic copolymer are deprotonated, so that the positive charge density and the total amount of the cationic copolymer are reduced, thereby electrically dissociating from the anionic polymer. The dissociated cationic copolymer forms a CO2 emulsion with supercritical CO2 and water. This process is called "in-situ release of CO2-philic cationic copolymer emulsifier when meeting water". At the same time, the anionic polymer selected by the present invention should not only be able to form nano-microspheres with the cationic copolymer, but also have the effects of drag reduction, permeability enhancement or slow release scale inhibition after release, rather than becoming a residual blockage in the pore system that requires additional degradation agent treatment.

[0038] When cationic copolymers and anionic copolymers are cross-linked to prepare nanospheres, the cross-linking agent used is used to cross-link other functional groups on the cations, but the cross-linking agent selected is a complex type (Cr cross-linking agent), and the bond formed is also a reversible complex bond, which can partially prolong the release time of the cationic polymer.

[0039] Beneficial effects of the present invention:

[0040] 1. The cationic copolymer provided by the present invention can make supercritical CO2 and water self-emulsify to form a stable emulsion under oil field formation conditions. The cationic copolymer has a positively charged hydrophilic chain segment structure, a CO2-philic chain segment structure and a propanol-type lipophilic chain segment structure, and has multiple affinity characteristics of hydrophilicity, lipophilicity and CO2-philicity in supercritical CO2 fluid. Therefore, the cationic copolymer provided by the present invention can form a CO2 / water emulsion when encountering formation water in a relatively harsh reservoir complex environment, and the emulsion undergoes a miscible process when encountering oil to form a pseudo-mixed state. This pseudo-mixed state can solve the key problem of the influence of formation water in the pore system, further enhance the effect of CO2 replacing crude oil in the matrix, and improve the recovery rate of crude oil.

[0041] 2. The nano-microspheres provided by the present invention can not only release cationic copolymers in situ when encountering water in the oil field reservoir, so that supercritical CO2 can generate emulsion in situ in the reservoir, but the dissociated anionic polymers should also have the effects of reducing drag, increasing permeability or slow-release scale inhibition, rather than becoming residual blockages in the pore system that require additional degradation agent treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1FTIR spectrum of the cationic copolymer prepared in Example 1 of the present invention.

[0043] Figure 2 This is a scanning electron microscope photograph of the nanospheres prepared in Example 1 of the present invention.

[0044] Figure 3 Schematic diagram of the test device used in Experimental Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The present invention will be further described below in conjunction with embodiments and drawings.

[0046] The raw materials and equipment used in the embodiments, comparative examples and experimental examples are all commonly used commercially available raw materials and equipment in the art, and their specific sources are not described here.

[0047] Example 1

[0048] A cationic copolymer is prepared by copolymerizing DMDAAC, propylene oxide and DMAEMA, wherein the molar ratio of DMDAAC, propylene oxide and DMAEMA is 4.6:1.9:3.3, and the average molecular weight of the cationic copolymer is 18000Da-22000Da;

[0049] The invention discloses a nanometer microsphere prepared by electrical adsorption of Na-PVS and the above cationic copolymer.

[0050] The preparation method of the above cationic copolymer and nano-microspheres is as follows:

[0051] S1. 0.02 g of AIBN initiator was dissolved in 5 mL of THF at room temperature to obtain an initiator solution;

[0052] S2. 7.5 g DMDAAC, 1.12 g propylene oxide and 5.2 g DMAEMA were dissolved in 10 mL DCM, the initiator solution prepared in S1 was added and mixed, nitrogen was passed through to deoxygenate, and the copolymerization reaction was stirred at 60°C to obtain a cationic copolymer.

[0053] During the reaction, the DCM solvent evaporates due to heat, and the remaining solvent is THF. The solution of the reaction product is diluted with THF to a concentration of 0.3% to obtain a cationic copolymer solution for use. After the cationic copolymer is pressed into a KBr tablet, an infrared spectrometer is used to analyze its functional groups. The infrared spectrum obtained is shown in the figure below. Figure 1 As shown. Figure 1 It can be seen that 2890cm -1 (-CH), 2830cm -1 (-CH2-OH), 1762cm -1The peak of (-CHOH) is the characteristic vibration peak of polypropylene glycol chain segment and poly(dimethylaminoethyl methacrylate) (PDMAEMA) chain segment; at the same time, 1050 -1 -1150cm -1 The vibration peak also proves the existence of ether groups (COC) on the polypropylene chain segments; 1500 -1 -1700cm -1 The vibration peaks prove the existence of quaternary ammonium functional groups on polydimethyldiallylammonium chloride (PDMDAAC). From the infrared analysis results, it can be seen that the cationic copolymer was successfully prepared in this example;

[0054] S3. Prepare a Na-PVS solution with a mass concentration of 0.075% with deionized water for later use, take 15mL of the Na-PVS solution and stir it at 800rpm at room temperature, take 4mL of the cationic copolymer solution obtained in step S2 and add it dropwise at a rate of 60 drops / min, and react with electrical adsorption under stirring to obtain a nanosphere dispersion. After concentrating and washing the nanospheres by centrifugation, a 0.035wt% low-concentration nanosphere dispersion is prepared, in which the solvent is deionized water, and a non-ionic stabilizer Pluronic F-127 is added to the dispersion to a final concentration of 0.02wt%, which can be stored for a long time, with a storage time of more than 6 months.

[0055] like Figure 2 As shown, the nanospheres prepared in this embodiment have a particle size of 200nm-400nm.

[0056] Example 2

[0057] A cationic copolymer is prepared by copolymerizing DMDAAC, NVP, propylene oxide and FDA, wherein the molar ratio of DMDAAC, NVP, propylene oxide and FDA is 12.3:19.3:4.5:1.2, and the average molecular weight of the cationic copolymer is 11000Da-14500Da;

[0058] The invention discloses a nanometer microsphere prepared by electrical adsorption of Na-PVS and the above cationic copolymer.

[0059] In this embodiment, the method for preparing the cationic copolymer and nanospheres is different from that in embodiment 1 in that:

[0060] In step S2, 2.5 g DMDAAC and 5 g NVP are used to replace 7.5 g DMDAAC in Example 1, and 5 g FDA is used to replace 5.2 g DMAEMA in Example 1;

[0061] In step S3, 12 mL of a 0.09% Na-PVS solution is reacted to prepare nanospheres, and the concentration of the low-concentration dispersion of nanospheres is 0.04 wt %;

[0062] Other conditions are the same as in Example 1.

[0063] Example 3

[0064] The first cationic copolymer is prepared by copolymerization of DMDAAC, propylene oxide and DMAEMA, wherein the molar ratio of DMDAAC, propylene oxide and DMAEMA is 4.6:1.9:3.3, and the average molecular weight of the cationic copolymer is 18000Da-22000Da. The preparation method is the same as step S1 and step S2 of embodiment 1.

[0065] The second cationic copolymer is prepared by copolymerization of DMDAAC, NVP, propylene oxide and FDA, wherein the molar ratio of DMDAAC, NVP, propylene oxide and FDA is 12.3:19.3:4.5:1.2, and the average molecular weight of the cationic copolymer is 11000Da-14500Da. The preparation method is the same as step S1 and step S2 of Example 2.

[0066] The invention discloses a nanometer microsphere prepared by electrical adsorption of Na-PVS and the two cationic copolymers.

[0067] In this embodiment, the method for preparing nanospheres is different from step S3 in embodiment 2 in that:

[0068] 2 mL of the first cationic copolymer solution and 2.5 mL of the second cationic copolymer solution are taken to replace the 4 mL of the cationic copolymer solution in Example 2, and the concentration of the low-concentration dispersion of nanospheres is 0.05 wt %;

[0069] Other conditions are the same as those in Example 2.

[0070] Example 4

[0071] A nanosphere prepared by cross-linking Na-PVS and the cationic copolymer prepared in Example 1, the preparation method is as follows:

[0072] S1. Prepare 0.075% Na-PVS solution for standby use, take 15 mL of Na-PVS solution and stir at 800 rpm at room temperature, take 4 mL of the cationic copolymer solution prepared in step S2 of Example 1 (the molar ratio of DMDAAC, propylene oxide and DMAEMA is 4.6:1.9:3.3) and add dropwise at a rate of 80 drops / min and stir thoroughly,

[0073] S2. After the suspension system is stable, 0.5 mL of 5% KCr(SO4)2 crosslinking agent diluent is added, and stirring is continued for 3 hours to prepare the final nanosphere suspension. The nanospheres are concentrated and washed by centrifugation to prepare a 0.1wt% nanosphere low concentration dispersion, and non-ionic stabilizer Pluronic F-127 is added to make its concentration 0.02wt% for long-term storage.

[0074] Example 5

[0075] This embodiment provides a cationic copolymer and nanospheres prepared therefrom. The preparation method is different from that of Example 1 in that 4.7 g TPA is used instead of 5.2 g DMAEMA, wherein the molar ratio of the reaction monomers DMDAAC, propylene oxide and TPA is 4.6:1.9:0.88, and other conditions are the same as those of Example 1.

[0076] Example 6

[0077] This embodiment provides a cationic copolymer and nanospheres prepared therefrom. The preparation method is different from that of Example 1 in that 5.7 g FDA is used instead of 5.2 g DMAEMA, the molar ratio of DMDAAC, propylene oxide and FDA is 4.6:1.9:1.36, and other conditions are the same as those of Example 1.

[0078] Example 7

[0079] This embodiment provides a cationic copolymer and nanospheres prepared therefrom. The preparation method is different from that of Example 1 in that the CO2-philic monomer DMDAAC is not added in step S2, and the molar ratio of other monomers remains unchanged.

[0080] Example 8

[0081] This embodiment provides a cationic copolymer and nano-microspheres prepared therefrom. The preparation method is different from that of Embodiment 1 in that the cationic monomer DMAEMA is not added in step S2.

[0082] Comparative Example 1

[0083] The difference between this comparative example and Example 1 is that the content of propylene oxide monomer in step S2 is changed so that the molar ratio of monomers DMDAAC, propylene oxide and DMAEMA is 4.6:3.1:3.3, and the average molecular weight of the cationic copolymer is 16000Da-22000Da;.

[0084] Comparative Example 2

[0085] A nanoparticle emulsifier with aminopropyltriethoxysilane (APTES) is used to improve the stability of CO2 foam dispersion system. The preparation process is derived from a published paper (Ning Chuang, Zhang Liwei, Tong Changbing, Jing Zhengzheng. Modified nano-SiO2 particles to improve CO2 foam stability. Contemporary Chemical Industry, 2024, 53(07): 1550-1554.)

[0086] The preparation method of the nanoparticle emulsifier having aminopropyltriethoxysilane (APTES) is as follows:

[0087] S1. 2.5 g of APTES was added to a suspension of 2.5 g of silica powder in 150 mL of toluene. The suspension was then stirred at room temperature for 12 h; thereafter, the solid was separated by centrifugation (3000 r / min, centrifugation time 10 min), followed by washing twice with ethanol (50 mL); finally, it was placed in an oven (1 h) and dried at 70 ° C to obtain surface-modified silica nanoparticles referred to as modified silica (MS) nanoparticles.

[0088] S2. Before the experiment, a pre-specified mass of nanomaterials (silicon dioxide, modified silica, or ZnO) and SDS were added to a specific amount of distilled water and then dispersed for 30 min using an ultrasonic probe to obtain a uniform nanofluid; the stability of the nanofluid was studied using the dynamic light scattering (DLS) method and a HORIBA Zetasizer SZ-100 zeta potential analyzer.

[0089] Comparative Example 3

[0090] A CO2-responsive particle emulsifier with dual functional groups for use in supercritical CO2 emulsification. The preparation process is based on a published paper (Li Xixi, Han Xia, Liu Honglai. Preparation of CO2-responsive particle emulsifier and study of its emulsification properties. Chinese Adhesives, 2019, 28(06): 1-4+17.)

[0091] The preparation method of the above-mentioned bifunctional modified CO2 responsive particle emulsifier is as follows:

[0092] S1. Take 1.0g of fumed silica particles and place them in a flask. After drying them in a vacuum oven at 100°C for 12h, add 20mL of anhydrous toluene pre-dried with 4A molecular sieves and perform ultrasonic treatment for 30min to evenly disperse the particles in toluene.

[0093] S2. Add 1.0 g of tetramethylguanidinepropyltrimethoxysilane and 1.0 g of hexadecyltrimethoxysilane to the above-mentioned toluene dispersion of silica, and react for 12 hours in an oil bath at 110°C and a nitrogen atmosphere to obtain a bifunctional modified CO2 responsive particle emulsifier.

[0094] Experimental Example 1

[0095] The nanospheres prepared in Examples 1-8 and Comparative Examples 1-3 were dried and then subjected to cationic polymer loading and embedding rate test experiments, and the particle sizes of the nanosphere samples were tested using a Zetasizer Nano LAB dynamic light scattering instrument from Malvern. The results are shown in Table 1.

[0096] Table 1 Measured data

[0097]

[0098] In the table, the calculation methods for the cationic copolymer loading rate and the cationic copolymer embedding rate are as follows:

[0099]

[0100]

[0101] As can be seen from the data in Table 1, Examples 1-7 all have a copolymer embedding rate of more than 34.9%. Comparative Example 1 has a relatively long polyoxypropylene bond in the copolymer long chain and a relatively low polymer water solubility, so the embedding rate is only 25.7%. The water solubility of the FDA added in Example 6 is relatively low, and it is difficult to be tightly entangled with the anionic polymer when preparing microspheres. Therefore, the loading rate is relatively low (26.4%), the coverage rate is also relatively low (31.4%), and the particle size of the formed microspheres is also relatively small, which is 168.6nm. Except for Example 6, the dispersed particle size of the other examples in 0.02wt% Pluronic F-127 solution is in the range of 317.4-476.8nm.

[0102] Experimental Example 2

[0103] The particle size of the nano-microspheres used for supercritical CO2 flooding deep in-situ self-emulsification was tested after being dispersed in deionized water, 1% NaCl, 0.02% Pluronic F-127 and 0.02% Pluronic F-127 + 1% NaCl solution for 6 hours of equilibrium. The nano-microspheres provided in Preparation Examples 1-6 were placed in different solutions and waited for 6 hours to allow them to swell and balance. The hydrodynamic diameter of the samples was tested using a Malvern dynamic light scattering instrument (Zetasizer Lab). The experimental data obtained are shown in Table 2.

[0104] Table 2 Nanosphere particle size

[0105]

[0106] In Table 2, the unit of each data is nm.

[0107] It can be seen from the data in Table 2 that the particle size of Examples 1-8 and Comparative Example 1 has obvious changes after standing for 6 hours under different solution environments. The particle size of all samples in 1% NaCl solution has increased, mainly because the nanospheres have swelled. On the contrary, after adding 0.02% Pluronic F-127, the particle size of the nanospheres is more stable, and the particle size does not change within 6 hours regardless of whether NaCl is present; however, when the NaCl concentration is 5%, 0.02% Pluronic F-127 cannot stabilize the nanospheres, and its concentration needs to be increased to 0.05%. Table 2 shows the particle size of Examples 1-8 and Comparative Example 1 under four different dispersion environments. Therefore, in the process of industrial implementation of the product, according to the mineralization of the formation water, Pluronic F-127 with a concentration of 0.02wt% to 0.05wt% can be used to regulate the swelling of the nanospheres and the time of releasing the cationic copolymer. More preferably, when the mineralization degree is in the range of 0-0.02%, the amount of Pluronic F-127 is 0.02 wt%, and when the mineralization degree is in the range of 0.02-0.05%, the amount of stabilizer is 0.05 wt%.

[0108] Example 3

[0109] The particle size of the nano-microspheres was tested by supercritical CO2 flooding in-situ self-emulsification. The nano-microspheres obtained in Examples 1-8 and Comparative Example 1 were dispersed in a 0.02% Pluronic F-127+1% NaCl solution (concentration 15 mg / ml), CO2 was introduced into the dispersion (20 ml / min), and the particle size change of the nano-microspheres after the introduction of CO2 was tested at different temperatures.

[0110] Table 3 Particle size change data

[0111]

[0112]

[0113] As shown in Table 3, Examples 1-6 show that as the CO2 injection time becomes longer, the stability of the nanospheres is inversely correlated with the temperature. When the test temperature is 65°C and 90°C, the particle size of the nanospheres increases significantly after 6 hours of CO2 injection, and swelling occurs. At 90°C, the particle size of some nanospheres cannot be measured after 6 hours of CO2 injection. Therefore, the temperature, pH sensitivity of the nanospheres and the CO2 injection time can be used to design the controlled release time of the nanospheres according to the actual situation. The particle size of Example 7 changes little after 18 hours of CO2 injection at 90°C, and the particles remain intact, which cannot meet the capacity of the controlled release cationic copolymer. Comparative Example 2 cannot be stably dispersed, and the particle size cannot be measured after 6 hours of CO2 injection (particle degradation). As can be seen from Table 3, when the temperature is 50°C, Examples 1-3, Example 6 and Example 8 have a good temperature response time range; when the temperature is 65°C, Examples 4 and 5 have a good temperature response time range; when the temperature is 90°C, Example 7 has a good temperature response time range.

[0114] Experimental Example 4

[0115] use Figure 3 The device shown measures the effect of the cationic copolymer and nano-microspheres prepared in Example 1 on the emulsification effect of supercritical CO2-deionized water at 65°C, 90°C and a pressure of 11±0.7MPa. A certain proportion of cationic polymer or nano-microspheres and a certain amount of H2O are placed in a high-temperature and high-pressure observation kettle, and after a certain proportion of supercritical CO2 is introduced, the emulsification of CO2-deionized water is observed after stirring for 5 minutes and 120 minutes, respectively.

[0116] Table 4 Emulsification

[0117]

[0118] As shown in Table 4, after stirring for 5 minutes, the cationic copolymer can make CO2-deionized water self-emulsify to form a stable emulsion at low and high concentrations, and the emulsification effect is better at high concentrations (1.23% and 1.4%). The temperature has no obvious effect on the emulsification effect of the cationic polymer. The nano microspheres do not have strong emulsification ability because they do not release free cationic polymers. After stirring the reaction for 120 minutes, emulsification reactions of samples 5-7 occur, and sample 8 is also further fully emulsified, proving that the nano microspheres release cationic polymers between 5 minutes and 120 minutes.

[0119] Experimental Example 5

[0120] The supercritical CO2 flooding deep in-situ self-emulsifying nano-microspheres prepared in Examples 1-8 and Comparative Examples 1-3 were used to conduct a simulation experiment of supercritical CO2 flooding in a tight reservoir, and the crude oil recovery factor was calculated by collecting the output fluid. The specific experimental process is as follows:

[0121] The experimental temperature was 70℃. The core used in the experiment was a cylindrical tight core (cross-section diameter 3.5cm, length 15cm) from the Chang 8 reservoir in Hongde, Ordos Basin, with a permeability of 21mD±0.1mD. The core was saturated with oil. The crude oil used in the experiment was produced by the Seventh Oil Production Plant of Changqing Oilfield Branch of PetroChina (obtained by three-phase separation at the Huansi Lian Water Injection Station), and the back pressure was 6.1MPa at a temperature of 70℃.

[0122] First, the core was flooded with supercritical CO2 until the pressure at both ends of the inlet and outlet was stable (about 2.5PV) and no crude oil continued to flow out; then, 1PV of nano-microspheres (0.2% wt) prepared in Examples 1-8 and Comparative Example 1 was injected, and both ends of the model were sealed and kept still for 24 hours; finally, supercritical CO2 was re-injected until no crude oil flowed out.

[0123] Table 5 Oil recovery rate

[0124]

[0125] As shown in Table 5, the recovery rate of the pre-supercritical CO2 flooding is 53.1-62.3%. This fluctuation is due to the inconsistency of the results of saturated crude oil and primary displacement at the beginning of each experiment, and this fluctuation belongs to the normal experimental range. When the CO2 bifunctional polyelectrolyte nanoparticles prepared by supercritical CO2 are injected into the embodiment 1-6, a small amount of crude oil is extracted (0-3.31%), mainly because the nano-microspheres are adsorbed on the rock surface after entering the core, improving its supercritical CO2 flow capacity. After the core is closed for 24 hours, some CO2 bifunctional polyelectrolyte nanoparticles undergo shell and core separation changes, further improving the oil displacement capacity. The recovery rate of the embodiment 1-8 in this process can reach 2.56-8.42%. Comparative Examples 2 and Comparative Examples 3 are both SiO2 nanoparticle surface modified, and their particles are not elastic and have a large particle size, so it is difficult to enter the core pores. Only 0.23PV and 0.11PV are injected respectively, and they cannot continue to be injected due to the excessive increase in pressure. Through the changes in crude oil recovery rate of two supercritical CO2 floodings, it can be seen that the supercritical CO2 flooding deep in-situ self-emulsifying nano-microspheres proposed by the present invention have a good effect in improving CO2 flooding in tight oil reservoirs.

[0126] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A cationic copolymer, prepared by copolymerizing monomer A, monomer B and monomer C, wherein the average molecular weight of the cationic copolymer is 1000Da-25000Da, The molar ratio of monomer A, monomer B and monomer C is (3-8):(1.5-2.5):(2-4), in, Monomer A is selected from at least one of dimethyldiallylammonium chloride, dimethylaminoethyl methacrylate, vinyl pyrrolidone or cationic acrylamide, monomer B is selected from propylene oxide, and monomer C is selected from at least one of dimethyldiallylammonium chloride, dimethylaminoethyl methacrylate, perfluoroacrylate, 1H,1H,2H,2H-perfluorodecyl acrylate or hexafluorobutyl methacrylate.

2. The cationic copolymer according to claim 1, characterized in that The molar ratio of monomer A, monomer B and monomer C is (3.5-6):(2-2.5):(3-3.6).

3. The cationic copolymer according to claim 1, characterized in that Monomer A is selected from dimethyldiallylammonium chloride, dimethylaminoethyl methacrylate or vinyl pyrrolidone; Monomer C is selected from dimethyldiallylammonium chloride or dimethylaminoethyl methacrylate; further preferably, when monomer A is selected from dimethyldiallylammonium chloride or dimethylaminoethyl methacrylate, monomer C is not required.

4. The cationic copolymer according to any one of claims 1 to 3, characterized in that The preparation method of the cationic copolymer is as follows: The initiator is dissolved in the first organic reagent to obtain an initiator solution, the monomer A, the monomer B and the monomer C are dissolved in the second organic solvent, the initiator solution is added and mixed, nitrogen is passed through to deoxygenate, and then the cationic copolymer is obtained by copolymerization through a hydrothermal reaction.

5. The cationic copolymer according to claim 4, characterized in that The initiator is selected from at least one of ammonium persulfate, 4,4-azobis(4-cyanovaleric acid) and azobisisobutyronitrile; The first organic reagent is tetrahydrofuran; The second organic reagent is selected from any one of cyclohexane, heptane, octane or kerosene; The hydrothermal reaction temperature is 45°C-65°C; The mass ratio of initiator to monomer B is (0.02-0.12):

1.

6. A nanosphere, wherein the nanosphere is prepared by reacting an anionic polymer and at least one cationic copolymer as provided in claims 1 to 5, wherein the molar ratio of the anionic polymer to the cationic copolymer is (1.28-0.69):1; The reactions include electrosorption and cross-linking; The anionic polymer is selected from at least one of sodium polyvinyl sulfate, polyacrylic acid, polyanionic cellulose or carboxymethyl cellulose; The average particle size of the nanospheres is 150nm-600nm.

7. The method for preparing nano-microspheres according to claim 6, wherein the cationic copolymer and the anionic polymer are respectively put into a solvent to prepare a cationic dispersion and an anionic dispersion, the cationic dispersion is added dropwise to the anionic dispersion, and the nano-microspheres are obtained by concentrating and washing after the reaction.

8. The preparation method according to claim 7, characterized in that: Deionized water is selected as the solvent in the cationic dispersion; deionized water is selected as the solvent in the anionic dispersion; further preferably, the mass concentration of the cationic copolymer in the cationic dispersion is 0.01wt%-1.10wt%, and the mass concentration of the anionic polymer in the anionic dispersion is 0.01wt%-1.50wt%; preferably, the dripping speed is 60-90 drops / min.

9. The preparation method according to claim 7, characterized in that: The preparation method also includes adding the nano-microspheres into a stabilizer solution to prepare a nano-microsphere dispersion with a mass concentration of 0.01wt%-1.50wt% for standby use; further preferably, the stabilizer is a Poloxmar type non-ionic surfactant; more preferably, the stabilizer concentration in the stabilizer solution is 0.02wt%-0.2wt%, and the solvent in the stabilizer solution is deionized water.

10. Application of nano-microspheres to improve oil recovery in supercritical CO2 flooding. The nanospheres are provided by any one of claims 6 or 7, or the nanospheres are prepared by the preparation method according to any one of claims 8 or 9, In the application, the nanospheres are put into supercritical CO2 and injected into the oil field reservoir, and the oil field reservoir has a crossflow channel; preferably, the mass ratio of the nanospheres to the supercritical CO2 is (0.05-4.5):100; further preferably, the nanospheres are put into the oil field reservoir directly and / or in the form of a nanosphere dispersion.

Citation Information

Cited By

  • CO2 response type multistage fluidity control gel particle and preparation method thereof

    CN120590588A